Estudo de viabilidade técnica do aproveitamento de água de chuva para fins não potáveis na Universidade Federal de Uberlândia, Uberlândia (MG) - Lopes, Gabriela Bernardi (2012)
Although the potable water is used for almost all activities, verify that the water supply of a building could be selective, presenting potable quality in activities that include direct contact with the human body, and non-potable quality in activities where there is only indirect use. In this sense, the water from precipitation could be harvested to attend of the non-potable demand, saving resources. Therefore, understands that the Federal University of Uberlândia (UFU), beyond to work in the development of research that aim the improvement of the population life quality, could also adopt technologies to promote the reduction of water consumption, based on conscious use of natural resources. Thus, this study aimed to verify the technical viability of a rainwater harvesting system for non-potable uses in a block of classes selected as object of study at UFU. The analysis was done under two aspects: under the quantitative point of view, verifying if the amount of rainwater collected supplied satisfactorily the demand for non-potable water in this block; and under the qualitative point of view, verifying if after disposal of the first millimeters precipitation, the rainwater collected has sufficient quality to attend this demand. During the research, the results indicated that the implementation of this system in the block in study probably would be viable of the quantitative point of view, because during the simulation, a tank of 344m3 attended 95% of annual demand for non-potable water in the block in study. Furthermore, the results also indicated that the implementation of this system in the block in study probably also would be viable of the qualitative point of view, because discarding the values found for the first 0,62 mm of precipitation and for the first rains after the dry winter, or even with a simplified treatment of decantation, all parameters studied during the research attended the water quality standards for non-potable uses.